Personnel Management Practices adopted by Principals in Administration of Secondary Schools in Awka Education Zone, Anambra State, Nigeria - Nnebedum Chidi; Abadi James Lucky; Obasi Henry Ikechukwu (ÜNİVERSİTEPARK Limited, 2019)
The study investigated the personnel management practices adopted by principals in the administration of secondary schools in Awka Education Zone, Anambra State, Nigeria. Two research questions guided the study and two hypotheses were tested at .05 level of significance. Mixed research design was employed for the study. The population of the study was comprised of 1,642 respondents, with 61 principals and 1,518 teachers from the Awka Education Zone of Anambra State. Multiple stage sampling technique was used to sample 485 respondents which consisted of 30 principals and 455 teachers. The instruments for data collection were questionnaire and interview. The instrument was validated by three experts who are lecturers in the Faculty of Education at Nnamdi Azikiwe University, Awka. The reliability of the instrument was ascertained using Cronbach alpha and it yielded reliability coefficients of .78 and .72 for Cluster I and Cluster II, respectively. The overall coefficient of the entire instrument was found to be .75. Data analysis was performed using mean and standard deviation. It was found that staff personnel management practices adopted by principals in their administration of secondary schools in the Awka Education Zone, Anambra State, include; motivating of teachers, encouraging team building so as to promote cohesiveness in the school, supervising teachers' activities, disciplining of teachers exhibiting misconduct behaviors, delegating duties to teachers, mentoring of teachers, rendering counseling services to teachers, recommending staff for promotion, and appraising staff performances. Based on the findings, conclusions and recommendations were made.